A Model of Cardiac Preparticipation Screening for Sports Competition in Indonesia: Challenges and Future Perspectives - Dwita Rian Desandri; Averina Octaxena Aslani (The Indonesian Heart Association, 2026)
Sudden cardiac death (SCD) among athletes remains a preventable tragedy, yet Indonesia lacks a national registry, standardized protocols, and systematic data amid rising coronary artery disease prevalence and regional cardiovascular risks unique to the Asia-Pacific. While countries like Italy have reduced SCD by 89% through mandatory electrocardiogram-based screening, Indonesia's Law No. 11 of 2022 mandates athlete health services without specifying cardiac preparticipation screening (CPS) details, resulting in inconsistent implementations across events like the quadrennial Pekan Olahraga Nasional (PON). This editorial proposes a feasible, cost-effective CPS model—history, physical exam, and 12-lead ECG using 2017 International Criteria—for PON athletes, delivered via Indonesian Heart Association, national sports committee, and ministry partnerships. Piloted with trained general practitioners and cardiologists at training centres, it aligns with WHO screening criteria, costs per athlete, and reserves echocardiography for high-risk cases. By generating Indonesia's first athlete SCD data, enhancing provider training, and enabling scalable nationwide rollout, this framework promises to quantify risks, avert fatalities, and position Indonesia as a leader in equitable sports cardiology for resource-constrained settings, transforming competitive sport from potential peril to unalloyed benefit.